(untitled) (International Journal of Environmental Sciences, 2025)
Background: Ayurgenomics explores the genetic and constitutional basis of individual health predispositions based on Ayurvedic Prakriti types. Kapha Prakriti, characterized by traits such as heaviness and sluggishness, has been traditionally associated with metabolic slowdown and weight gain. These features may predispose individuals to metabolic risks, including pre-diabetes Objective: To investigate the association between Kapha Prakriti and pre-diabetic markers, including fasting blood sugar (FBS), body mass index (BMI), and familial history of diabetes, from an Ayurgenomics perspective. Methods: This cross-sectional study involved 50 adults aged 30–60 years, assessed for Prakriti using a validated Ayurvedic questionnaire. FBS and BMI were measured using standard procedures. Statistical analyses examined correlations between Prakriti dominance and metabolic risk markers. Results: The cohort comprised 56% Kapha-dominant individuals, with the remainder Pitta and Vata. The Kapha group showed higher mean FBS (118 ± 4.5 mg/dL) and BMI (28.6 ± 2.3 kg/m²). Significant positive correlations were observed between Kapha Prakriti and both FBS (r=0.65, p<0.01) and BMI (r=0.72, p<0.01). Pitta and Vata groups demonstrated weaker, non-significant associations. Conclusion: The study highlights the Ayurgenomic link between Kapha Prakriti and increased pre-diabetic risk markers, reflecting genetic and constitutional predispositions to metabolic dys-regulation. Incorporating Prakriti assessment into early screening may facilitate personalized prevention strategies, bridging Ayurvedic principles with modern genomics to combat metabolic disorders.